PENGARUH BEBAN KERJA, MOTIVASI DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA PEGAWAI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) KOTA BALIKPAPAN - Anggreini Retor, Meinita; Hasan, Syahril; Yuliani, Tutik (Jurnal GeoEkonomi, 2025)
This research aims to determine the direct influence of workload variables, motivation and work discipline on job satisfaction of civil service agency employees and human resource development in the city of Balikpapan. This research used a sample of 47 respondents with a questionnaire data collection method and analysis tools assisted by SPSS software. The results show that (1) Workload directly has a positive and significant effect on Job Satisfaction of Balikpapan City Personnel and Human Resources Development Agency (BKPSDM) employees; (2) Motivation directly has a positive and significant effect on Job Satisfaction of Balikpapan City Personnel and Human Resources Development Agency (BKPSDM) employees; (3) Work Discipline directly has a positive and significant effect on Job Satisfaction of Balikpapan City Personnel and Human Resources Development Agency (BKPSDM) employees.